Optimization of Halal Bioadsorbent Particle Size from Pyrolysis Products of Coconut Trunk Sawdust for the Purification of Virgin Coconut Oil (VCO) - Andi Aladin; Rismawati Rasyid; Takdir Syarif; Siti Nur Annisa; Nurul Faradillah (Candela Edutech Indonesia, 2025)
One of the critical challenges in the virgin coconut oil (VCO) industry is the selection of crude VCO filtration media that must be strictly guaranteed halal, since VCO is widely used as a food ingredient and for medicinal purposes. In this study, coconut trunk sawdust waste was utilized as a raw material and converted into charcoal through a pyrolysis process. The resulting charcoal was then applied as a bioadsorbent for crude VCO filtration. This article reports the effect of bioadsorbent particle size variations, specifically -/20, 20/50, 50/100, 100/140, 140/200, and 200/- mesh, to determine the optimum particle size that provides the highest VCO clarity. The experiments were conducted under constant conditions with a bioadsorbent-to-VCO ratio of 2% (g/mL) and a filtration time of 10 minutes. The optimum particle size was obtained at 50/100 mesh (200 µm), which resulted in maximum VCO clarity with a turbidity value of 1.48 NTU. Based on this optimum particle size, the filtered VCO showed desirable quality parameters, including lauric acid content of 51.96%, total suspended solids of 5.77%, density of 0.95 g/mL, total plate count (TPC) <10 CFU/mL, and moisture content of 0.0235%. These characteristics meet both the Indonesian National Standard (SNI) and international standards of the Asian and Pacific Coconut Community (APCC). Moreover, the resulting VCO exhibited better clarity than commercial VCO filtered using paper or cloth media (1.59 NTU), while also ensuring halal integrity through the use of bioadsorbent derived from pyrolyzed coconut trunk sawdust